2013
DOI: 10.1097/jcp.0b013e31828393cb
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Intravenous Heroin on the Hypothalamic-Pituitary-Adrenal Axis Response

Abstract: Heroin dependence is associated with a stressful environment and with dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis. The present study examined the acute effects of intravenous heroin versus placebo on the HPA axis response in heroin-dependent patients. Twenty-eight heroin-dependent patients in heroin-assisted treatment and 20 age- and sex-matched healthy participants were included in a controlled trial in which patients were twice administered heroin or saline in a crossover design, and healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 34 publications
(26 reference statements)
1
32
0
1
Order By: Relevance
“…As previously reported [11], a single dose of DAM instantly reduces state-anxiety, craving scores, and stress reactivity, as measured by the secretion of ACTH and cortisol in heroin-dependent patients, and indicating a dampening effect of stress-related responses. Furthermore, we recently observed that patients even revealed increased state-anxiety and craving scores after the injection of saline [3], indicating an experimentally induced state of acute withdrawal.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…As previously reported [11], a single dose of DAM instantly reduces state-anxiety, craving scores, and stress reactivity, as measured by the secretion of ACTH and cortisol in heroin-dependent patients, and indicating a dampening effect of stress-related responses. Furthermore, we recently observed that patients even revealed increased state-anxiety and craving scores after the injection of saline [3], indicating an experimentally induced state of acute withdrawal.…”
Section: Discussionmentioning
confidence: 51%
“…Our group previously found suppressed cortisol concentrations and reduced craving scores after acute methadone administration in heroin-dependent patients [9]. We also demonstrated a normalized HPA axis response as well as a decrease in negative feelings such as anxiety and craving when heroin-dependent patients received their regular dose of DAM [10, 11]. This dampening effect on negative emotions highlights the regulatory effect of acute DAM administration and illustrates how compliance is maintained.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…This compulsion is frequently driven by craving which is triggered by stress and drug-related stimuli (Sinha et al 2006, Walter et al 2013. The mesolimbic dopamine pathway-dopamine cells in the ventral tegmental area projecting into the nucleus accumbens-is considered essential for drug reward and drug-seeking behavior (Volkow et al 2011).…”
Section: Introductionmentioning
confidence: 99%